Food safety requirements in case of short food supply chain - Nagy – Pércsi, Kinga (Studia Mundi – Economica, 2018)
It can be stated according to the relevant literature that the health related characteristics of the food products and the ethical values relating to the sustainable development and consumption gains on a growing importance among the preferences of the consumers. The article introduce the different possible types of Short Food Supply Chains, the various food safety requirements relating to them and the opinion of some relevant conventional and organic farmers about the prevailing of rules. The aim of this article is to give a picture of the evolution of the food safety regulations, than a broad review of the different SFSC types, and to find the differences between the farmers’ group. It investigates the most important characteristics of direct sale in the light of the recent food safety requirements among the surveyed farmers. The surveys were made as a preliminary research for a more comprehensive study.
Keywords: local food; Short Food Supply Chain; food-safety requirements; consumer preferences and trust